Impact of retinopathy of prematurity on ocular structures and visual functions. Issue 2 (21st October 2014) - Fielder, Alistair; Blencowe, Hannah; O'Connor, Anna; Gilbert, Clare
Abstract : The preterm baby may develop ophthalmic sequelae which can be due to prematurity per se, due to retinopathy of prematurity (ROP) or due to neurological damage. Focusing on the former two, we discuss how in high-income countries the risk of sight-threatening ROP is largely confined to babies <1000 g birth weight (BW), whereas in low-income or middle-income countries babies exceeding 2500 g BW can be blinded. The effects of prematurity and ROP are presented as regional and global estimates of acute-phase ROP and the consequent mild/moderate and severe visual impairment. We discuss sequelae and how they affect the eye and its shape, strabismus and finally consider their impact on visual functions, including visual acuity, the visual field, colour vision and contrast sensitivity.